The structure of the world: metaphysics and representation - Steven French (Oxford ; Oxford University Press, 2014)
Steven French articulates and defends the bold claim that there are no objects in the world. He draws on metaphysics and philosophy of science to argue for structural realism - the position that we live in a world of structures - and defends a form of eliminativism about objects that sets laws and symmetry principles at the heart of ontology.--
Keywords: Structuralism; Realism; Sciences